E-PC101: an electronic clinical decision support tool developed in South Africa for primary care in low-income and middle-income countries. (20th February 2019) - Yau, Matthew; Timmerman, Venessa; Zwarenstein, Merrick; Mayers, Pat; Cornick, Ruth Vania; Bateman, Eric; Fairall, Lara
Abstract : Health technology is increasingly recognised as a feasible method of addressing health needs in low and middle-income countries (LMICs). Primary Care 101, now known as PACK (Practical Approach to Care Kit), is a printed, algorithmic, checklist-based, comprehensive clinical decision support tool. It assists clinicians with delivering evidence-based medicine for common primary care presentations and conditions. These assessment and treatment guides have been adopted widely in primary care clinics across South Africa. This paper focuses on the process of designing, developing, and implementing a digital version of the clinical decision support tool for use on a tablet computer. Lessons learnt throughout its development and pilot implementation could apply to the creation of electronic health interventions and the digitisation of clinical tools in LMICs.